Pengaruh Bunyi Bahasa Jepang Terhadap Penulisan Kata – Kata Berbahasa Indonesia Oleh Penutur Bahasa Jepang - Aliffia Rachmawati; Ismatul Khasanah (Universitas Negeri Semarang, 2022)
The form of a language can change over time given its dynamic nature; broadly speaking, that is the discussion in the field of sociolinguistics. Mastery of more than one language causes deviations, one of which is when expressing words from certain languages ​​by inserting sounds from other languages. This phenomenon is called phonological interference. This study takes data from Japanese speakers who speak Indonesian on the YouTube page. This study aims to analyze forms and describe the factors that cause phonological interference when speaking Indonesian. This research uses the descriptive qualitative analysis method. After going through the analysis process, it was found that the forms of phonological interference that occur include: addition, subtraction, letter replacement, and diphthongs. Based on the analysis of the forms of phonological interference that occur, it can be seen that the causal factors are differences in nasal sounds between Indonesian and Japanese, the use of open syllables, differences in writing methods, the absence of certain fellowship patterns, the duration of studying Indonesian and the presence of factors other than linguistics. So it can be said that the first language of a person greatly affects the pronunciation of the individual's second language.